THE INDONESIAN AGRICULTURAL PERFORMANCES UNDER CHINA-ASEAN FREE TRADE AREA: GO UP OR GO DOWN? Case of Agriculture Raw Material and Food Product - Nasrudin Nasrudin; Budiyanto Budiyanto (Jurnal Sosio Agribisnis, 2017)
As an agricultural country, the Indonesian agricultural sector should obtain a positive impact of the regional economic integration. Since in 2004 by the Early Harvest Program (EHP) of China-ASEAN Free Trade Agreement (CAFTA), most agricultural commodities have lowered tariff, indeed some have been zero percent.Unfortunately, the performance of the agricultural sector has not shown tangible improvement. Then beforethe rates was released for all commodities, should be evaluated and re-defined policies that should be taken. This paper purposesto examine the impact of the implementation of CAFTA on the Indonesian agricultural performances. The objectives will be achieved by compare the performance preand post-CAFTA; predict the performance if CAFTA is fully implemented, by performing simulations and econometric models. By using time series data 1990-2011, agriculture can be divided into two categories; agricultural raw materials and food products. The estimation result of econometric modeling by simultaneous equations, the Indonesian agricultural sector performance after CAFTA is not better than before implementation. Predicted will decrease when the entire rates later free. Keywords: agriculture raw material; foods product; agriculture performance; economic integration